2018
DOI: 10.1093/mnras/sty1923
|View full text |Cite
|
Sign up to set email alerts
|

KiDS-SQuaD: The KiDS Strongly lensed Quasar Detection project

Abstract: New methods have recently been developed to search for strong gravitational lenses, in particular lensed quasars, in wide-field imaging surveys. Here, we compare the performance of three different, morphology-and photometry-based methods to find lens candidates within the Kilo-Degree Survey (KiDS) DR3 footprint (440 deg 2 ). The three methods are: i) a multiplet detection in KiDS-DR3 and/or Gaia-DR1, ii) direct modeling of KiDS cutouts and iii) positional offsets between different surveys (KiDS-vs-Gaia, Gaia-v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 40 publications
0
57
0
Order By: Relevance
“…In addition, the completed KiDS survey will cover an area of 1350 square degrees. We plan to apply our method to these completed KiDS data, together with that of Spiniello et al (2018), to find lensed quasars. Applying other complementary methods as Hartley et al (2017) SVM will aid in maximizing the exploration of the parameter space.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the completed KiDS survey will cover an area of 1350 square degrees. We plan to apply our method to these completed KiDS data, together with that of Spiniello et al (2018), to find lensed quasars. Applying other complementary methods as Hartley et al (2017) SVM will aid in maximizing the exploration of the parameter space.…”
Section: Discussionmentioning
confidence: 99%
“…The size and homogeneity of this sample is required for the surveys primary science drivers, which include placing strong constraints on both the distribution of matter across cosmic time and the cosmological parameters of the universe through weak-lensing measurements; the subtle distortions introduced in galaxy shapes by cosmic shear (e.g., Hildebrandt et al 2017). At the same time, the combined power of the survey's superb image quality and wide area makes KiDS optimal for strong-lensing studies (Napolitano et al 2016;Petrillo et al 2017;Spiniello et al 2018). OmegaCAM has a one square degree field of view, with pixels that have an angular scale of 0.21 arcseconds, and KiDS will survey a total of ∼1350 square degrees in four optical bands (u, g, r and i) by the end of observations in 2019.…”
Section: Data From the Kilo-degree Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…The depth of KiDS, ∼ 25 mag in the r band (5σ), its multiwavelength ugri coverage, and availability of overlapping VIKING data at a similar depth (Edge et al 2013), make this survey an ideal resource for quasar science. This remains however a very much uncharted territory in KiDS, and only three studies so far presented QSO-related analyses based on this survey: Venemans et al (2015) focused on very high-redshift (z ∼ 6) quasars found in a combination of KiDS and VIKING data, Heintz et al (2018) studied a heavily reddened QSO identified in KiDS+VIKING, while Spiniello et al (2018) selected QSO-like objects over the KIDS DR3 footprint to search for strong-lensing systems.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Hartley et al (2017) have used a technique based on Support Vector Machines (SVMs) and applied it to KiDS. Instead Spiniello et al (2018) focused on the search of lensed quasars in KiDS using 3 different morphology based methods.…”
Section: Introductionmentioning
confidence: 99%